Review of Sociosexuality Curricular Content for Individuals With Developmental Disabilities. (September 2019) - Wolfe, Pamela S.; Wertalik, Jennifer L.; Domire Monaco, Sarah; Gardner, Stephanie; Ruiz, Salvador
Human sexuality encompasses aspects of physiology and emotions. The need for sociosexuality education for individuals with developmental disabilities (DD) is widely acknowledged; yet, there is little known about what topics of sexuality are presented. This review identified curricular content used in comprehensive, commercially available sexuality curriculum for individuals with DD. Results indicated that biological aspects such as anatomy and physiology were taught in all the curriculums; however, issues related to culture and society were less frequently present. The need for specific sexuality content is discussed as well as future implications.